Race and reconciliation : essays from the new South Africa - Herwitz, Daniel (Public worlds, 2003)
Seeking the timeless through the timely, Daniel Herwitz brings the vast resources of the philosophical essay to bear on the new realities of post-apartheid South Africafrom racial identity to truth commissions, from architecture to film and television. A public intellectuals reflections on public life, Herwitzs essays question how the new South Africa has constructed its concepts of reconciliation and return.